The effect of value congruence on employees’ performance at Khomas Directorate of Education in Windhoek, Namibia - Joseph V. Hauﬁla; Nikodemus Angula (BOHR International Journal of Advances in Management Research, 2026)
The study examined the impact of value congruence on employees’ performance at the Khomas Directorate of Education in Windhoek, Namibia. It used a quantitative research approach to assess the relationship between value congruence and service delivery, job satisfaction, motivation, emotional intelligence (EI), and teamwork. The study used a correlational research design, which examines the relationship between value congruence and employee performance without manipulating variables. The study used descriptive statistics, regression analysis, and Statistical Package for the Social Sciences (SPSS) version 29 software to analyze data. A chi-squared test was used to examine the relationship between value congruence and employees’ performance, with a significance level of 0.05. The results were presented in graphs and tables. The results showed no significant relationship between value congruence and service delivery. However, it found a significant relationship between value congruence and job satisfaction, leading to higher performance and customer satisfaction. The study also revealed a significant relationship between value congruence and employees’ EI, influenced by positive organizational values. The findings suggest that organizations should recognize and respect employees’ values, use appropriate leadership, promote teamwork and collaboration, uphold ethical and motivational values, and provide further training to management on employee evaluation.